Biologia de Tetranychus mexicanus (McGregor) (Acari: Tetranychidae) em três espécies de Annonaceae - Sousa, Josilene M De; Gondim Jr, Manoel G C; Lofego, Antônio C [UNESP] (Sociedade Entomológica do Brasil, 2010)
The mite Tetranychus mexicanus (McGregor) is considered a pest of a variety of plant species in the Americas. Although this mite apparently causes economic damage to Annonaceae, little is known about its biology. Here we studied the biology of T. mexicanus on soursop (Annona muricata), sweetsop (Annona squamosa) and araticum (Annona coriaceae). The first two species are the most important economical Annonaceae species in northeast Brazil; araticum is commonly found in the region, but not commercially explored. The mites were collected in the field from leaves of A. muricata and maintained in the laboratory for six months on detached leaves of A. muricata, A. squamosa and A. coriaceae, respectively, before observations started. Tetranychus mexicanus developed more slowly on A. squamosa than on the two other hosts, but oviposition was considerably lower on A. coriaceae. As indicated by the calculated life table parameters, biotic potential was higher on A. muricata than on the other hosts. Despite the observed differences in the T. mexicanus biology on the different evaluated hosts, development and reproduction were satisfactory in all of the hosts used.
Biology of Tetranychus mexicanus (McGregor) (Acari: Tetranychidae) on Three Species of Annonaceae
Keywords: Mite; tetranychid; Annona; life table